1993
DOI: 10.1051/lait:199313
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisme de la caséine Κ de trois races bovines françaises et aptitude à la coagulation

Abstract: (Reçu le 11 mai 1992; accepté le 27 octobre 1992) Résumé -Les études réalisées sur des laits individuels de 3 races bovines traditionnelles exploitées en France (Montbéliarde, Normande et Tarentaise) confirment l'intérêt du polymorphisme de la caséine lC (x-On) sur l'aptitude des laits à la coagulation par la présure. L'homozygote BB contient plus de caséine totale. Il est plus riche en x-On, Il présente un temps de gélification par la présure plus court que l'homozygote AA ou les hétérozygotes AC, BC, AB et s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
(19 reference statements)
3
6
0
2
Order By: Relevance
“…The greater curd firmness of Mo cows' milk is essentially due to its higher nitrogen content, as observed by a number of authors [16,22] and confirmed herein. The higher curd firmness of Modicana milk with the same nitrogen content could be attributed firstly to the polymorphism of casein κ, as evidenced in individual [9] or mixed milks [14]. Indeed, it is a known fact that the casein κ variant B is sharply more frequent in Modicana cows [6,13] than in Holstein cows [12] and it has been confirmed in this trial.…”
Section: Discussionsupporting
confidence: 65%
“…The greater curd firmness of Mo cows' milk is essentially due to its higher nitrogen content, as observed by a number of authors [16,22] and confirmed herein. The higher curd firmness of Modicana milk with the same nitrogen content could be attributed firstly to the polymorphism of casein κ, as evidenced in individual [9] or mixed milks [14]. Indeed, it is a known fact that the casein κ variant B is sharply more frequent in Modicana cows [6,13] than in Holstein cows [12] and it has been confirmed in this trial.…”
Section: Discussionsupporting
confidence: 65%
“…This study confirmed the very beneficial effect of variant B of κ-and β-caseins on the rheological properties of coagulated milk [12,30]. However, the results of this trial seem to indicate that this beneficial effect on milk coagulation does not have any repercussions on the physico-chemical and sensory characteristics of the corresponding cheeses.…”
Section: Effect Of Genetic Variantssupporting
confidence: 73%
“…Yet, few studies have considered the intrinsic effect of the floristic composition of forage, an issue often raised by cheesemakers and the relevance of which to cheese quality has been suggested by some authors [14,25]. It is also a recognized fact that certain genetic variants of milk caseins have an influence on its clotting capacities [12,30,39]: this is true for variant B of β-and, especially, of κ-caseins, resulting in shorter clotting time and firmer curd. To our knowledge, no studies have been conducted on the effect of these variants on the sensory characteristics of cheese, whereas it is known that other genetic variants can perceptibly alter the physico-chemical and sensory characteristics of cheese [13,28].…”
Section: Introductionmentioning
confidence: 99%
“…The smaller casein micelle diameter gives a denser and firmer casein network [89,108], which improves fat retention in the coagulum. Such was the case with the association of variant B of β and κ-casein in the Normande cattle breed [35,91] or with the variant A of α s1 -casein, compared with defective variants, in goats [107] or with the variant C of α s1 -casein in sheeps' milk [101]. The example of variant C of β-casein in the Tarentaise cattle breed is a good illustration of the mechanisms that can be at the origin of the texture differences noted.…”
Section: Proteins and Fat Modificationsmentioning
confidence: 92%
“…The beneficial effect of variant B of κ and β-caseins on the rheological properties of clotted milk and on cheese yield has been evidenced in numerous studies [35,54,72]. Variant B reduces clotting and curd-firming times and leads to firmer rennet curd than variant A.…”
Section: Effect Of Genetic Variantsmentioning
confidence: 98%